The Effectiveness of the Discovery Learning Model on Poetry Writing Ability - Arya Miza Amin; Desi Sukenti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
The reason for choosing the discovery learning model because it is an active learning model that can help the student’s writing skills. By using this learning model, students can learn to think, analyze, and solve problems. The purpose of the research is to find the effect of the discovery learning model on students’ ability in writing a poetry at Sekolah Menengah Atas (SMA) Negeri 1 Pangkalan Kerinci. This research was experimental research with a form of quasi-experimental design. The sample of this study was two classes, the control class and the experimental class, from Grade X SMA Negeri 1 Pangkalan Kerinci. The number of each class consisted of 32 students. In the experimental class, discovery learning is applied as a treatment, while the control class still uses a conventional learning model. The data analysis used descriptive statistics. The results of the study revealed that learning using the discovery learning model in students’ ability in writing poetry obtains the value of learning completeness at 86.7% which is higher than the conventional learning model. Based on the significant value of Sig (2-tailed) between discovery learning and the ability to write poetry is 0.000 < 0.0. It means that there is a significant effect between discovery learning and student’s ability in writing poetry. From the results of the study, it can be concluded that the writing ability in the poetry of SMAN 1 Pangkalan Kerinci students is high by using discovery learning.